Inflammatory Disease Affecting the Central Nervous System in Dogs: A Retrospective Study in England (2010–2019) - Gonçalves, Rita; De Decker, Steven; Walmsley, Gemma; Butterfield, Sarah; Maddox, Thomas W. (Frontiers in Veterinary Science, 2022)
The epidemiology of inflammatory diseases affecting the central nervous system (CNS) in dogs is largely unknown. We aimed to report the relative proportion of different causes of inflammatory disease affecting the CNS in dogs and identify predictors for infectious vs. immune-mediated conditions and predictors for the most common diseases affecting the brain and the spinal cord. This was a retrospective cohort study over a 10-year period in 2 referral institutions using multivariable and multinomial logistic regression for identification of risk factors. In total, 1,140 client-owned dogs diagnosed with inflammatory disease affecting the CNS were included. Fifteen different diagnoses were identified, with immune-mediated (83.6%) disease being more common than infectious conditions (16.4%). The most common immune-mediated conditions diagnosed were meningoencephalitis of unknown origin (47.5%) and steroid-responsive meningitis–arteritis (30.7%), and the most common infectious conditions were discospondylitis (9.3%) and otogenic intracranial infection (2.2%). Older age (p < 0.001, OR = 1.019, 95% CI: 1.014–1.024), higher body weight (p < 0.001, OR = 1.049, 95% CI: 1.025–1.074), male sex (p = 0.009, OR = 1.685, 95% CI: 1.141–2.488), longer duration of the clinical signs before presentation (p < 0.001, OR = 1.011, 95% CI: 1.006–1.017), progressive nature of the clinical signs (p < 0.001, OR = 2.295, 95% CI: 1.463–3.599), identification of a possibly associated preceding event (p = 0.0012, OR = 1.93, 95% CI: 1.159–3.213), and hyperesthesia on presentation (p < 0.001, OR = 2.303, 95% CI: 1.528–3.473) were associated with a diagnosis of infectious diseases. Our data shows that immune-mediated diseases are more common than infectious conditions as a cause for inflammatory CNS disease in dogs. The risk factors for the most common diagnoses were identified from signalment, history, and findings of the physical and neurological examinations to give valuable information that can guide clinicians with their investigations.